2018
DOI: 10.1111/dom.13508
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dapagliflozin versus comparators on renal endpoints in the real world: A multicentre retrospective study

Abstract: The antiproteinuric effect of dapagliflozin is confirmed here for the first time by real-world data. Despite a mild decline in eGFR, there was no evidence of clinically relevant worsening in renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Selection of the primary endpoint may also be disputable, but prioritization of endpoints in observational research is much less important than in RCTs, because real‐world studies are intrinsically hypothesis‐generating and endpoints were not tested hierarchically. As CVOTs have demonstrated the way that achievement of combined targets is associated with better cardiovascular outcomes in T2D, we speculate that, among patients receiving SGLT2is or GLP‐1RAs, those attaining combined treatment goals may benefit more from the cardiovascular protection conveyed by such drugs. Unlike the populations of CVOTs, however, the population addressed in the present study comprised mainly patients without a history of CVD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Selection of the primary endpoint may also be disputable, but prioritization of endpoints in observational research is much less important than in RCTs, because real‐world studies are intrinsically hypothesis‐generating and endpoints were not tested hierarchically. As CVOTs have demonstrated the way that achievement of combined targets is associated with better cardiovascular outcomes in T2D, we speculate that, among patients receiving SGLT2is or GLP‐1RAs, those attaining combined treatment goals may benefit more from the cardiovascular protection conveyed by such drugs. Unlike the populations of CVOTs, however, the population addressed in the present study comprised mainly patients without a history of CVD.…”
Section: Discussionmentioning
confidence: 96%
“…Availability of such comparative assessment could contribute to clinical decision‐making and therapeutic tailoring. Interestingly, change in HbA1c, BW and BP can occur independently; change in HbA1c and reduction in BW are unrelated during therapy with GLP‐1RAs, whereas reduction in blood pressure is unrelated to glycaemic control during therapy with SGLT2is …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dedicated software was developed to extract all relevant anonymized patient information for placement into a clinical research form without manual intervention. Suitability of this data collection approach for performing real‐world comparative effectiveness studies has been demonstrated extensively …”
Section: Methodsmentioning
confidence: 99%
“…Suitability of this data collection approach for performing real-world comparative effectiveness studies has been demonstrated extensively. [19][20][21][22] The study was promoted by the University Hospital of Padova and approved by the respective ethical committees of each participating centre. As data were anonymized at time of automatic extraction, making patient re-identification impossible, no informed consent was required according to national regulations concerning retrospective studies.…”
Section: Methodsmentioning
confidence: 99%